Therapy and outcomes of cardiac implantable electronic devices infections. (23rd June 2021) - Perrin, Tilman; Deharo, Jean-Claude
Abstract: Cardiac implantable electronic device (CIED) infection causes significant morbidity and mortality without appropriate treatment. It can present as incisional infection, pocket infection, systemic CIED infection, or occult bacteraemia. Complete percutaneous CIED extraction (excepted in case of incisional infection) and appropriate antibiotic therapy are the two main pillars of therapy. Device reimplantation, if needed, should be delayed sufficiently to allow control of the infection. Here, we address the differences in prognosis according to the clinical scenario and the different treatment options.